Evaluation of Brain Targeting and Mucosal Integrity of Nasally Administrated Nanostructured Carriers of a CNS Active Drug, Clonazepam - Hend Mohamed Abdel-Bar; Amal Youssef Abdel-Reheem; Gehanne A.S Awad; Nahed Daoud Mortada (Frontiers Media S.A., 2013)
PURPOSE: The aim of the study was to target clonazepam, a CNS active drug, to the brain through the non-invasive intranasal (in) route using of nanocarriers with proven safety METHOD: in clonazepam nanocarriers were prepared by mixing isopropyl myristate, Tween 80, Cremophor EL or lecithin, polyethylene glycol 200, propylene glycol or ethanol in different ratios with water. in-vitro characterization of the nanocarriers was done by various methods including: polarized light microscopy, particle size determination, viscosity measurements and drug release studies. in-vivo study comparing intranasal and intravenous administration was performed. The drug targeting efficiency (DTE %) and direct nose to brain transport percentage (DTP %) were calculated and nasal integrity assessment was carried out. RESULTS: The obtained formulae had particle size below 100 nm favoring rapid direct nose to brain transport and the time for 100% drug release (T100%) depended on systems composition. Plasma Tmax of clonazepam nanostructured carriers varied from 10-30 min., while their brain Tmax did not exceed 10 min, in comparison with 30 min for iv solution. Although there was no significant difference (p>0.05) between the plasma AUC0-∞ of the different tested nanocarriers and intravenous one, the increase in brain AUC 0 -∞ of different nasal formulations in comparison to that of iv administration (3.6 -7.2 fold) confirms direct nose to brain transport via olfactory region. Furthermore, DTE and DTP% confirmed brain targeting of clonazepam following intranasal administration. CONCLUSION: The results confirmed that intranasal nanocarriers were proved to be safe alternative for iv clonazepam delivery with rapid nose to brain transport. This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.